The Influence of Lecture and Game Media on Knowledge and Attitudes about Anemia in Adolescent Girls - Fazdilah, Ayu Cindy; Azzahra, Kania Ekayanti; Khoiriyah, Nur; Mahabatillah, Desty; Rahmawati, Dinar Putri (Urecol Journal. Part C: Health Sciences, 2025)
Background: Anemia is a medical condition characterized by low hemoglobin levels in the blood. It remains a nutritional problem among adolescents, particularly among teenage girls. This condition can lead to decreased immunity, concentration issues in learning, and academic performance. One of the preventive measures against anemia is nutrition education that is engaging and tailored to the characteristics of adolescents, which can enhance knowledge and attitudes as a means of preventing anemia. Objective: This study aims to analyze the effect of nutrition education on the knowledge and attitudes of teenage girls regarding anemia using lecture and game media. Methods: The design used is a quasi-experimental Non-Equivalent Control Group Design involving 48 respondents from SMPN 15 Kota Cirebon, divided into two groups: the lecture education group and the game group. The variables analyzed include respondent characteristics, nutritional status, knowledge, and attitudes. Data analysis was performed using the Mann-Whitney test to examine differences between groups and the Wilcoxon test to assess differences before and after the education intervention. Results: There was a significant difference in knowledge scores between the lecture education group and the game group after the educational activities (p = 0.000). The increase in knowledge scores in the lecture group was significantly higher compared to the game group (p = 0.005). Additionally, this study showed no significant difference in attitudes between the two groups. Conclusion: Nutrition education can significantly improve knowledge about anemia among adolescents. The use of lecture media in this study was found to be more effective than game media.